Analisis Dikeluarkannya Fly Ash Bottom Ash (FABA) dari Kategori Limbah B3 - Azahra Nabila Nasution, Shafira; Fillo Sofia, Tasya; Hakemah Binti Mahari, Mu`ezzah; Wulandari (Indonesian Journal of Law and Justice, 2026)
In accordance with Government Regulation Number 22 of 2021, which replaced Government Regulation Number 101 of 2014, this study examines the legal basis and environmental implications of removing Fly Ash Bottom Ash (FABA) from the hazardous waste category. The research applies a normative legal method using statutory and conceptual approaches, supported by the analysis of relevant primary and secondary legal materials. The findings indicate that the government justifies the reclassification based on the relatively stable characteristics of FABA generated from high-temperature combustion processes, considerations of industrial cost efficiency, and its potential utilization within a circular economy framework. Nevertheless, the policy raises significant environmental concerns, particularly regarding the risk of heavy metal contamination affecting soil, water, and air. It also prompts debate over the potential weakening of strict liability and precautionary principles as stipulated in Law Number 32 of 2009. The study concludes that clearer technical standards, strengthened derivative regulations, and transparent monitoring mechanisms are essential to safeguard environmental protection and ensure long-term sustainability.